Miniaturization of microstrip and cpw-fed uwb printed antennas with band rejection characteristics - Shareef, Wessam Zayd (2010)
The tremendous developments over the recent years in wireless communications applications led to the urgent need for the innovation of new technologies capable of vast data transfer rates at very low power consumption levels. Such technologies also require large portions of the frequency spectrum. Ultra wideband (UWB) technology is being considered as a solution to address these issues. This technology attracted high attention especially after the allocation of 7.5 GHz spectrum bandwidth between 3.1 GHz and 10.6 GHz for the UWB civil applications by the Federal communication Commission (FCC). As is the case in conventional wireless communication systems, an antenna plays a significant role in achieving successful transmission and reception of information in the form of data packets using UWB systems. This thesis presents two new designs of notched band Ultra-Wideband printed antennas using microstrip and coplanar waveguide-fed configurations. Simple techniques of perforation the substrate and modifying the ground planes and radiator patches are used to achieve ultra wideband for the designed antennas with small structure. Narrow Arch-shaped slot was introduced to the patch of the proposed antennas to obtain the band rejection function around the 5.4 GHz frequency to avoid the interference with WLAN standards like IEEE 802.11a and HIPERLAN/2 Both UWB antennas were developed and analyzed by a 3D electromagnetic simulator. To confirm the simulation results, the two proposed antennas were fabricated on FR-4 substrate with dielectric constant of 4.4 and the experimental measurements were carried out using a network vector network analyzer (Anritsu 37347D). The analysis indicated a fairly good agreement between simulation and measurement. The measured bandwidth of the proposed microstrip-fed UWB antenna is ranging from 2.62 GHz up to 12.7 GHz with a return loss no more than -10 dB excluding a notched frequency starting from 5.1 GHz to 6 GHz. The overall size of the antenna is 20 × 21 × 1.6 mm3 The Measurement results of the proposed cpw-fed UWB antenna showed that this antenna has operational bandwidth starting from 2.45 GHz to 10.9 GHz with return loss better than -10 dB excluding the notched band from 4.83 GHz to 5.97 GHz. The antenna features the same compact size of the microstrip antenna (20 × 21 × 1.6 mm3). In the addition to the required UWB bandwidth, both designed antennas are exhibit high radiation efficiency, stable group delay and omni-directional pattern which makes them suitable for UWB portable wireless devices with their compact size feature.